(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2024)
Ekphrastic poetry is a poetic reinterpretation of a visual artwork. There are numerous poems, songs, and lyrics written with inspiration from paintings, sculptures, or photographs. An ekphrastic poem can immortalize a work of art adding a new perspective to it. This paper looks at the tradition of Ekphrastic poetry as a genre and explores Vincent van Gogh’s famous painting The Starry Night through the light of Anne Sexton’s popular ekphrastic poem “The Starry Night”. It observes how Sexton’s poem artfully attempts to capture the spirit of Van Gogh’s painting through words. It also suggests how combining poetry with visual art can enrich both art and literature.